Pellagra Syndrome in Geriatric Patient: Insights from Pathogenesis and Diagnosis - Raharjo, Fajar Maulana; Soenarti, Sri; Winoto, Eden Suryoiman; Adriansyah, Vito; Aditya, Muhammad Reva (Clinical and Research Journal in Internal Medicine, 2026)
Pellagra syndrome is a chronic niacin deficiency disease that is often underdiagnosed. We report a case of an 83-year-old woman presenting with the four classic symptoms (4D) of pellagra: dermatitis (Casal’s necklace), diarrhea, dementia, and a risk of death if left untreated. The patient also had severe malnutrition, multiple infections, and a history of stroke for five years. The diagnosis was established based on clinical findings and a history of inadequate nutritional intake. Management included fluid therapy, antibiotics, medical rehabilitation, enteral and parenteral nutrition, as well as niacin supplementation. Following treatment, the patient showed clinical improvement, including stabilization of hemoglobin levels. This case highlights the importance of early detection and understanding the pathogenesis of Pellagra syndrome to improve patient outcomes and quality of life. Keywords: Casal’s Necklace, Dementia, Malnutrition, Niacin, Pellagra syndrome